Thyroidectomy in Pediatric Patients with Graves' Disease: A Systematic Review of Postoperative Morbidity - Zaat, Annabel S. (Eur Thyroid J, 2021)
BACKGROUND: Graves' disease (GD) is the most common cause of hyperthyroidism. In children, the overall relapse frequency after treatment with antithyroid drugs is high. Therefore, many pediatric GD patients eventually require thyroidectomy as definitive treatment. However, the postoperative complications of thyroidectomy in pediatric GD patients are poorly reported. OBJECTIVE: To identify the frequency of short- and long-term postoperative morbidities after thyroidectomy in pediatric GD patients. METHODS: A systematic review of the literature (PubMed and Embase) was performed to identify studies reporting short- and long-term postoperative morbidities after thyroidectomy in pediatric GD patients according to the PRISMA guidelines. RESULTS: Twenty-two mainly retrospective cohort studies were included in this review evaluating short- and long-term morbidities in 1,424 children and adolescents. The frequency of transient hypocalcemia was 22.2% (269/1,210), with a range of 5.0–50.0%. The frequency of permanent hypocalcemia was 2.5% (36/1,424), with a range of 0–20.0%. Two studies reported high frequencies of permanent hypocalcemia, 20.0 (6/30) and 17.4% (9/52), respectively. The 20% frequency could be explained by low-volume surgeons in poorly controlled GD patients. Only 21 cases of permanent hypocalcemia were reported in the 1,342 patients included in the other 20 studies (1.6%). Transient and permanent recurrent laryngeal nerve injury were reported less frequently, with frequencies between 0–20.0 and 0–7.1%, respectively. Infection, hemorrhage/hematoma, and keloid development were only rarely reported as postoperative complications. CONCLUSION: The results of this systematic review suggest that thyroidectomy is a safe treatment option for pediatric GD patients. The minority of patients will experience transient and benign morbidities, with hypocalcemia being the most common transient postoperative morbidity. Permanent postoperative morbidities are relatively rare.